Constructivism in Action: A Dynamic Group Process in Defining and Applying Principles of Social Justice - Tanupreet Suri; Leslie Woolson; Arianna Trott; Marty Apodaca; M. Kathryn Brammer; Dèsa Karye Daniel; Diane Lacen; Thomas A. Chávez (Teaching and Supervision in Counseling, 2021)
As a part of a Multicultural course, students in a doctoral program at a university in the Southwest worked together to synthesize a definition of social justice. The constructivist process implemented in this educational experience represented social justice in action, through co-construction of shared meaning. This definition, centered on Iris Young’s (2004) Five Faces of Oppression, resulted in the following: Social justice is addressing oppression, violence, exploitation, marginalization, powerlessness, and cultural imperialism through counselors’ efforts and advocacy, while promoting a critical perspective of the culture of silence. Social Justice is an active, effective change on micro- and macro-levels to alter social systems and institutions, whereby improving human rights and access to resources. Social justice is actively engaging in education, advocacy, critical thinking, systemic change, and client empowerment in order to diffuse mechanisms of oppression for the purpose of assisting clients in reaching their human potential.
Keywords: counselor education; social justice; constructivism